Mechanical properties and microstructure of plant fiber reinforced BFS-MS geopolymer: an orthogonal design approach - Zhu, Zunquan; Chang, Dongming; Zhu, Yong; Li, Jie; Zhang, Kai; Lu, Haifeng (Frontiers in Earth Science, 2025)
Foundation pit engineering usually encounters the problems of foundation reinforcement and mud soil (MS) disposal. This study proposes a solidification technology utilizing blast furnace slag (BFS)-MS based geopolymer, enhanced by renewable plant fibers, to achieve resource utilization of MS. The key parameters including activator modulus, alkali content, water-to-solid ratio, and MS replacement rate were systematically optimized through orthogonal experimental design. Based on considering the mechanical properties and economy, the pretreated wood (WF), jute (JF) and bamboo (BF) fibers were incorporated respectively to study the influence of plant fiber type and content on the mechanical properties of geopolymer. The results demonstrated that the optimal parameters for BFS-MS precursors were activator modulus 1.7 and alkali content 0.2. The BFS-MS geopolymer under the optimal ratio of 28 days can reach 43.56 MPa, maintaining excellent potential for engineering application even at 30% MS replacement. At 1.0% dosage, WF, JF and BF enhanced the 28-day compressive strength by 27.80%, 12.35% and 29.05% respectively. The microstructural analysis revealed that geopolymer gels derived from BFS hydration dominated early strength development, while potentially active minerals in MS contributed to later stage strength enhancement. This study provides theoretical and technical foundations for MS utilization and fiber-reinforced geopolymer design in sustainable construction practices.